Introduction to the issue on multitarget tracking - Mallick, Mahendra; Vo, Ba-Ngu; Kirubarajan, Thia; Arulampalam, Sanjeev (IEEE journal of selected topics in signal processing, 2013)
Multitarget tracking has a long history spanning over 50 years and it refers to the problem of jointly estimating the number of targets and their states from sensor data. Today, multitarget tracking has found applications in diverse disciplines, including, air traffic control, intelligence, surveillance, and reconnaissance (ISR), space applications, oceanography, autonomous vehicles and robotics, remote sensing, computer vision, and biomedical research. During the last decade, advances in multitarget tracking techniques, along with sensing and computing technologies, have opened up numerous research venues as well as application areas. The multitarget tracking problem in the presence of false alarm and sensor probability of detection less than unity is much more complex than the standard filtering problem. Apart from process and measurement noises in the dynamic and measurement models, respectively, one has to contend with much more complex sources of uncertainty, such as the measurement origin uncertainty, data association, false alarm, missed detections, and births and deaths of targets. The goal of this special issue is to explore recent advances in the theory and applications of multitarget tracking with a focus on novel algorithms and methods.